Vertigo Associated With Cochlear Implant Surgery: Correlation With Vertigo Diagnostic Result, Electrode Carrier, and Insertion Angle - Weinmann, Charlotte; Baumann, Uwe; Leinung, Martin; Stöver, Timo; Helbig, Silke (Frontiers in Neurology, 2021)
Objective: Vertigo is a common side effect of cochlear implant (CI) treatment. This prospective study examines the incidence of postoperative vertigo over time and aims to analyze influencing factors such as electrode design and insertion angle (IA). Study Design: Prospective study Setting: Tertiary referral center, academic hospital Patients: 29 adults were enrolled and received a unilateral CI using one of six different electrode carriers, which were categorized into: “structure-preserving” (I), “potentially structure-preserving” (II) and “not structure-preserving” (III). Intervention: Subjective vertigo was assessed by questionnaires at five different time-points before up to six months after surgery. Participants were divided into four groups depending on the time of the presence of vertigo before and after surgery. Preoperatively and 6 months postoperatively, a comprehensive vertigo diagnosis consisting of Romberg test, Unterberger test, subjective visual vertical, optokinetic test, video head impulse test and caloric irrigation test was performed. In addition, the IA was determined and patients were divided in two groups (<430°; ≥430°). Main Outcome Measures: Incidence of vertigo after CI surgery (group 1). Correlation of subjective vertigo with electrode array categories (I-III) and IA. Results: 45.8% of participants experienced new vertigo after implantation. Based on the questionnaire data a vestibular origin was suspected in 72.7%. Results did not show significant correlation with subjective vertigo for any of the performed tests. In group 1 with postoperative vertigo 18% of patients showed conspicuous results in quantitative analysis of caloric irrigation test despite the fact that category I or II electrodes were implanted, which are suitable for structure preservation. Average IA was 404° for the overall group, and 409° for group 1. There was no statistically significant correlation between IA and perceived vertigo. Conclusions: Though vertigo after CI-surgery seems a common complication, the test battery used here could not objectify the symptoms. Further studies should clarify whether this is due to the multifactorial cause of vertigo or to the lack of sensitivity of the tests currently in use. The proof of reduced probability for vertigo when using atraumatic electrode carrier was not successful, nor was the proof of a negative influence of the insertion depth.